2022
DOI: 10.5812/ijpbs-120159
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Online Group-mindfulness and Acceptance‐based Therapy and Cognitive-behavioral Therapy on Misophonia

Abstract: Background: Misophonia is a disorder in which people show negative emotions such as anger, disgust, and anxiety about certain sounds, such as mouth and nose sounds, as well as some repetitive sounds. This disorder has a high prevalence and causes many problems for patients. Objectives: This study aimed to examine and compare the effectiveness of two therapies, including online group-mindfulness and acceptance‐based therapy (OG-MACT) and online group-cognitive-behavioral therapy (OG-CBT) in patients with misoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The other ways of managing misophonia are compassion training, distress tolerance, and acceptance-based therapies Arch 2015, Ferrer-Torres andGiménez-Llort 2022). In a study by Ghorbani et al (2022), the effects of online acceptance and commitment therapy (ACT) and online CBT methods on the symptoms and quality of life of misophonia were examined and compared. Although no significant difference was found between the two treatment methods, it was observed that the symptoms of misophonia, anxiety, stress, and depression decreased, and distress tolerance increased (Ghorbani et al 2022).…”
Section: Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The other ways of managing misophonia are compassion training, distress tolerance, and acceptance-based therapies Arch 2015, Ferrer-Torres andGiménez-Llort 2022). In a study by Ghorbani et al (2022), the effects of online acceptance and commitment therapy (ACT) and online CBT methods on the symptoms and quality of life of misophonia were examined and compared. Although no significant difference was found between the two treatment methods, it was observed that the symptoms of misophonia, anxiety, stress, and depression decreased, and distress tolerance increased (Ghorbani et al 2022).…”
Section: Therapiesmentioning
confidence: 99%
“…In a study by Ghorbani et al (2022), the effects of online acceptance and commitment therapy (ACT) and online CBT methods on the symptoms and quality of life of misophonia were examined and compared. Although no significant difference was found between the two treatment methods, it was observed that the symptoms of misophonia, anxiety, stress, and depression decreased, and distress tolerance increased (Ghorbani et al 2022). In the literature, ACT provided a decrease in both symptoms of misophonia and depressive symptoms in a 12-year-old girl (Petersen and Twohig 2023) and a decrease in symptoms of misophonia in a 17-year-old boy (Schneider and Arch 2017).…”
Section: Therapiesmentioning
confidence: 99%